Understanding Responses to Political Conflict Interactive Effects of the Need for Closure and Salient Conflict Schemas. (article). - Golec, Agniezka
Two studies examined the relationship between the need for cognitive closure and preferences for conflict-resolution str in 2 different samples of elite political actors. Although research has suggested that high need for closure should be associated with competitiveness, the authors argue that this relationship should be strongest among political actors with a hostile conflict schema, or representation of what a conflict is and how it should be dealt with. The authors provide evidence for this hypothesis using archival survey data on American foreign-policy officials' attitudes toward international conflict at the height of the Cold War (Study 1) and their own data on the relationship between need for closure and conflict-strategy preferences among samples of activists from 2 political parties in Poland: a centrist party with a reputation for cooperativeness and an extremist party with a reputation for confrontation (Study 2). The broader implications of these findings are discussed. -- (from the author).